Learning English Grammar through Jazz Chants viewed from students’ attitude in SD IT Hidayatullah, Kota Bengkulu - Lisa Rakhmanina (Literary Criticism, 2018)
Grammar teaching has always been a controversial issue of language teaching, since the teaching technique seems tense and boring. Here the researcher’s focus is a way to learn grammar through rhymes and chants to young learners. The researcher presents a technique through Jazz Chants that involving the learners to identify and understand the grammatical point in content. Jazz Chants is a rhyme and repetition in a situational context based on everyday life situation. Each of the chant is accompanied by the target structure that indicates the specific focus of the material. The study is aimed at comparing the students’ grammar aspect through Jazz Chants and understanding the attitude of the students in teaching English grammar through Jazz Chants. The sample is the students of the sixth grade consisted of 50 students in SD IT Hidayatullah, Kota Bengkulu. The design of the study was mixed method design. The quantitative data were carried out from grammar test and the students’ attitude toward teaching English grammar. The qualitative data came from a learning log, an interview, and teacher’s journal. A pre-test and post-test design, 8 lesson plan, and an attitude questionnaire were applied in the study. Percentage, mean, standard deviation, and t-test were used to analyze the data quantitatively. The study findings were as follow: 1. The students’ English grammar ability after using Jazz chants were significantly higher than before their use. 2. The students’ attitude toward teaching English grammar were rated as good. Keywords: English Grammar, Jazz chant, language, teaching technique